1996
DOI: 10.1152/ajprenal.1996.270.5.f845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic NO synthesis inhibition on RPF, GFR, UNa, and vasoactive hormones in healthy humans

Abstract: Animal studies have implicated an important role of nitric oxide (NO) in the regulation of blood pressure, renal hemodynamics, and renal excretion of sodium. NG-monomethyl-L-arginine (L-NMMA) is a specific, competitive inhibitor of NO synthesis interfering with NO synthase. The purpose of the present study was to investigate the effect of L-NMMA on renal plasma flow (RPF), glomerular filtration rate (GFR), urinary sodium excretion (UNa), fractional sodium excretion (FENa), fractional lithium excretion (FELi), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 0 publications
9
72
1
Order By: Relevance
“…These transporters are responsible for the majority of transepithelial sodium reabsorption in the proximal tubules (1,5,45,57). Micropuncture studies in rats have shown that sodium nitroprusside added to the tubular perfusate significantly decreases proximal tubular fluid reabsorption (14,61), and studies in humans have shown that systemic administration of NOS inhibitors have antinatriuretic effects associated with marked decreases in FE Li (4,6,36). These in vitro and in vivo experiments suggest that NO exerts a tonic inhibitory effect on proximal tubular sodium reabsorption.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These transporters are responsible for the majority of transepithelial sodium reabsorption in the proximal tubules (1,5,45,57). Micropuncture studies in rats have shown that sodium nitroprusside added to the tubular perfusate significantly decreases proximal tubular fluid reabsorption (14,61), and studies in humans have shown that systemic administration of NOS inhibitors have antinatriuretic effects associated with marked decreases in FE Li (4,6,36). These in vitro and in vivo experiments suggest that NO exerts a tonic inhibitory effect on proximal tubular sodium reabsorption.…”
Section: Discussionmentioning
confidence: 88%
“…Excess NO has been shown to inhibit the Na-K-ATPase and the type 3 sodium/proton exchanger (NHE3) in proximal tubular cell lines (20,33,46), and micropuncture studies in rats have shown that NO significantly decreases proximal tubular fluid reabsorption (14,61). These micropuncture data from rats are supported by studies in humans showing that systemic administration of NOS inhibitors decreases fractional excretion of sodium (FE Na ) and fractional excretion of lithium (FE Li ; an index for the delivery of tubular fluid out of the proximal tubules) (4,6,36). Finally, an experiment in rats has shown that a subpressor dose, i.e., a dose without effects on mean arterial pressure (MAP), of the NOS inhibitor N G -nitro-L-arginine methyl ester (L-NAME) has significant antinatriuretic effects (30).…”
mentioning
confidence: 92%
“…9,26 The hypothesis may therefore be advanced that the interaction between NO and ET A receptor activity observed in the present study is not the expression of a balance between baseline endogenous NO and ET but rather of an increased ET production due to NOSI alone. The degree of NOSI-induced increase in circulating ET-1 has been shown to range from 0% to 20% in human studies, associated with a 5% to 7% increase in MAP, 4,27 and from 40% to 70% in rat experiments, 25,28 in which MAP rose by Ն20% to 30%. Such changes in circulating ET-1 are much smaller than those that occur after anesthesia in rats, 29 and they are in any case still below the vasoconstrictor threshold both in vitro 30 and in vivo, as indicated for systemic and renal circulation in studies in humans undergoing ET-1 infusion.…”
Section: Montanari Et Al Effects Of L-name and Bq-123 In Human Kidneymentioning
confidence: 96%
“…1 When tonic NO production is acutely abrogated by NO synthase inhibition (NOSI) in animals and humans, vasoconstriction takes place, with a dose-dependent increase in mean arterial pressure (MAP) and vascular resistance in many organs, including renal circulation. [1][2][3] In human kidney, we and others [3][4][5] have previously shown that NOSI with low-rate systemic infusion of N G -monomethyl-L-arginine (L-NMMA) or N G -nitro-L-arginine methyl ester (L-NAME) may reduce effective renal plasma flow (ERPF), renal blood flow (RBF), glomerular filtration rate (GFR), and Na excretion independently of any apparent change in MAP. Both withdrawal of tonic NO production and amplification of underlying endogenous vasoconstrictor systems, such as angiotensin II (Ang II) and sympathetic nervous system, may participate, at least under certain experimental conditions, in renal vasoconstriction secondary to NOSI.…”
mentioning
confidence: 99%
“…48 In normal animals and humans, short-term inhibition of NOS results in renal vasoconstriction and reduced renal plasma flow. 49,50 In contrast, NOS inhibition in cirrhotic rats with ascites does not affect renal blood flow or function 51,52 despite an increased systemic pressor effect. 53 Furthermore, renal vasoconstriction may occur in the presence of increased glomerular nitrite production 54 and increased urinary nitrate excretion 55 in ascitic patients compared with compensated nonascitic cirrhotics.…”
Section: The Pathophysiology Of Hrs and Its Role In Preventionmentioning
confidence: 98%